Almost sure convergence for weighted sums of WNOD random variables and its applications to non parametric regression models. Issue 16 (18th August 2018) - Yan, Jigao
ABSTRACT: In this article, some results on almost sure convergence for weighted sums of widely negative orthant dependent (WNOD) random variables are presented. The results obtained in the article generalize and improve the corresponding one of J. Lita Da Silva. [(2015), "Almost sure convergence for weighted sums of extended negatively dependent random variables." Acta Math. Hungar. 146 (1), 56–70]. As applications, the strong convergence for the estimator of non parametric regression model are established.